Are Your Employees Hopeful at Work? The Influence of Female Leadership, Gender Diversity and Inclusion Climate on Japanese Employees’ Hope - Kim, Soyeon (Frontiers in Psychology, 2022)
There are two well-known truths about Japan: One is that Japan is one of the most advanced economies, which takes pride in its highly advanced technology, social infrastructure and system; the other is that Japan ranks lowest among Organisation for Economic Co-operation and Development countries when it comes to women’s social participation. Even though the Japanese government has initiated programs to promote female participation and advancement in society, these initiatives have not yet borne remarkable fruit. This study intends to address this issue by investigating the effectiveness of female leadership in Japan, specifically its effect on organizations’ gender diversity and inclusion (D&I) climate and employees’ task-related positive attitudes. Synthesizing social information processing theory and social identity theory, the study examines 306 Japanese employees working with their female supervisors in medium- and large-sized manufacturing companies. The findings show that female ambidextrous leadership contributes to shape and strengthen a gender D&I climate and ultimately enhances employees’ hope at their work. In addition, the positive effect of a gender D&I climate on employees’ hope is the same for all employees regardless of gender. The findings clarify the role of female leadership and the underlying psychological mechanism through which female leadership influences employees’ positive work attitudes. This first empirical study in Japan contributes to the research on female leadership and D&I management.